(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The study aims to identify the factors that are most consistently associated with swimming speed, movement efficiency, and athletes’ long-term participation. The data sources consisted of peer-reviewed international journal articles retrieved from reputable scientific databases based on predetermined inclusion and exclusion criteria. Data were collected through a systematic literature search, article screening, and data extraction procedures, while the collected information was analyzed using descriptive quantitative synthesis by comparing and integrating findings across the selected studies. The synthesis revealed that muscular strength, explosive power, metabolic capacity, pacing quality, and kinematic stability emerged more consistently as the primary determinants of swimming performance than recovery interventions alone. Furthermore, findings regarding swimmer’s shoulder, breakout-phase biomechanics, and stroke distribution indicate that competitive success cannot be explained solely by physical capacity. Psychosocial variables, particularly the coach-created motivational climate, also demonstrated a significant influence on the retention of young athletes. These findings confirm that swimming performance is multidimensional; therefore, effective training programs should integrate physical periodization, technical refinement, competition strategies, and injury prevention within a comprehensive framework. Nevertheless, this study is limited by its reliance on published articles from 2021–2025 and the heterogeneity of research designs, participant characteristics, and performance measures across the included studies, which may affect the generalizability of the synthesized findings.